Kingdom of Swaziland : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of Swaziland. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that the macroeconomic conditions have recently deteriorated in Swaziland. In 2016, two shocks-a prolonged drought and a sharp decline in South African Customs Union (SACU) receipts-severely hit the economy, while an expansionary fiscal policy worsened fiscal and external balances. Growth in 2016 stagnated, as agricultural productions declined, and headline inflation increased sharply, mostly owing to rising food prices. Fiscal policy remains on an expansionary course, while the monetary stance has tightened. Despite a pickup in SACU revenue, the 2017 budget envisages a continuation of large fiscal deficits, and further increase in public debt.